ERODIBILITAS TANAH (K) PADA BERBAGAI TUTUPAN LAHAN DI DESA BARU KECAMATAN SILAT HILIR KABUPATEN KAPUAS HULU - Injiliana, Lidia; Widiastuti, Tri; Riyono, Joko Nugroho (JURNAL HUTAN LESTARI, 2020)
Land degradation will result in widespread land damage, especially damage to forest land. Changes in land use from permanent vegetation to intensive agricultural land make the soil more easily eroded. One of the determining factors of erosion is soil erosion and soil cover vegetation. Soil erodiability is the average amount of soil lost each year per unit of the index, while the land cover is useful to protect the soil from the threat of damage by erosion and improve soil conditions. The research area located in Silat Hilir Sub-District of Kapuas Hulu Regency is a strategic area of the district from the point of economic importance. The Upper Kapuas Statistics Agency says there is a change in land use from year to year. The changes occurred not only in the increase in land use but also on changes in land use. The purpose and benefit of this research are to know the class of soil erodiability as well as to provide information on the class of land erodiability in The New Village of Silat Hilir District of Kapuas Hulu Regency. The value of soil erodiability is calculated using the Wischmeier and Smith formulas (1978) and determined based on the overlay of two maps, namely the land type map and the land cover map. Soil erodibility on various land cover in Silat Hilir Sub-District of Kapuas Hulu sub-district consists of 4 classes of land erodiability, among others: class 1 (very low), class 2 (low), class 4 (somewhat high), and class 5 (high).Keywords: Erodibility, Land Cover, Soil